Current view on the functional regulation of the neuronal K+-Cl− cotransporter KCC2 - Medina, Igor; Friedel, Perrine; Rivera, Claudio; Kahle, Kristopher T.; Kourdougli, Nazim; Uvarov, Pavel; Pellegrino, Christophe (Frontiers in Cellular Neuroscience, 2014)
In the mammalian central nervous system, the inhibitory strength of chloride (Cl-)-permeable GABAA and glycine receptors (GABAAR and GlyR) depends on the intracellular Cl- concentration ([Cl-]i). Lowering [Cl-]i enhances inhibition, whereas raising [Cl-]i facilitates neuronal activity. A neuron’s basal level of [Cl-]i, as well as its Cl- extrusion capacity, is critically dependent on the activity of the electroneutral K+-Cl- cotransporter KCC2, a member of the SLC12 cation-Cl- cotransporter (CCC) family. KCC2 deficiency compromises neuronal migration, formation and the maturation of GABAergic and glutamatergic synaptic connections, and results in network hyperexcitability and seizure activity. Several neurological disorders including multiple epilepsy subtypes, neuropathic pain, and schizophrenia, as well as various insults such as trauma and ischemia, are associated with significant decreases in the Cl- extrusion capacity of KCC2 that result in increases of [Cl-]i and the subsequent hyperexcitability of neuronal networks. Accordingly, identifying the key upstream molecular mediators governing the functional regulation of KCC2, and modifying these signalling pathways with small molecules, might constitute a novel neurotherapeutic strategy for multiple diseases. Here, we discuss recent advances in the understanding of the mechanisms regulating KCC2 activity, and of the role these mechanisms play in neuronal Cl- homeostasis and GABAergic neurotransmission. As KCC2 mediates electroneutral transport, the experimental recording of its activity constitutes an important research challenge; we therefore also, provide an overview of the different methodological approaches utilized to monitor function of KCC2 in both physiological and pathological conditions.